Effect of Power Plant Capacity on the CAPEX, OPEX, and LCOC of the CO2 Capture Process in Pre-Combustion Applications. (July 2021) - Ashkanani, Husain E.; Wang, Rui; Shi, Wei; Siefert, Nicholas S.; Thompson, Robert L.; Smith, Kathryn; Steckel, Janice A.; Gamwo, Isaac K.; Hopkinson, David; Resnik, Kevin; Morsi, Badie I.
Highlights: Aspen Plus was used to perform techno-economic analysis of a CO2 capture process in seven different power plants with capacities ranging from 54 to 543 MW. Four physical solvents (polyethyleneglycol polydimethyl siloxane, PEGPDMS-1 and PEGPDMS-3, and ionic liquids (ILs) [bmim][Tf2 N] and [emim][Tf2 N]) were employed for CO2 capture from a typical sulfur-free shifted fuel gas streams under high pressure (5.14 MPa) in a wide range of temperature from 0 to 50 °C. The CO2 capture process included a countercurrent packed-bed absorber and three flash drums for solvent regeneration using the pressure-swing option. Increasing the power plant capacity decreased LCOC of the CO2 capture process. The OPEX contribution to the LCOC was greater than the that of the CAPEX. Abstract: Recently, there has been a renewed focus in the gasification research community on the development of small-scale modular gasifiers that can take advantage of local solid feedstocks, and modular-scale synthesis reactors, which can generate local fuels, chemicals, and fertilizers. To fully realize the benefits of modular-scale systems, however, it is crucial for the cost of the required CO2 capture to remain low, even at reduced flow rates compared with large-scale IGCC-CCS power plants. In this work, the CO2 capture process in seven pre-combustion power plant with capacities ranging from 54 to 543 MW was modeled using Aspen Plus v8.8. Four physical solvents (PEGPDMS-1, PEGPDMS-3, [bmim][Tf2 N], and [emim][Tf2 N]) were used to capture CO2 from a typical sulfur-free fuel gas streams in a countercurrent packed-bed absorber. The experimental solubilities of the fuel gas components in the solvents were modeled using the PC-SAFT Equation-of-State. For each power plant capacity, the absorber flooding was checked for all solvents under the operating conditions used. The simulation results showed that increasing power plant capacity from 54 to 543 MW increased the operating expenditure (OPEX) from 2.6 to 30 MM$/year and the capital expenditure (CAPEX) from 10 to 58 MM$. On the other hand, increasing power plant capacity decreased the OPEX and CAPEX expressed in $/ton CO2 captured, reducing the levelized cost of the CO2 capture (LCOC) of the process from 12.50 to 7.58 $/ton CO2 captured, which was attributed to the increased tonnage of the CO2 removed